2013
DOI: 10.1002/da.22145
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias to Threat Faces in Severe Mood Dysregulation

Abstract: Background We used a dot-probe paradigm to examine attention bias toward threat (i.e., angry) and happy face stimuli in Severe Mood Dysregulation (SMD) vs. healthy comparison (HC) youth. The tendency to allocate attention to threat is well established in anxiety and other disorders of negative affect. SMD is characterized by the negative affect of irritability, and longitudinal studies suggest childhood irritability predicts adult anxiety and depression. Therefore, it is important to study pathophysiologic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
63
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 54 publications
7
63
1
1
Order By: Relevance
“…Lastly, the results of our cognitive behavioral model are in line with evidence that both depressed adults (Foland-Ross and Gotlib, 2012; Foland-Ross et al, 2013; Gotlib et al, 2004) and adolescents (Hankin et al, 2012; Hommer et al, 2013) show biased processing to affectively negative material compared to healthy controls. We observed greater drift rates in depressed individuals on both correct and error responses (see Figure 2 and Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…Lastly, the results of our cognitive behavioral model are in line with evidence that both depressed adults (Foland-Ross and Gotlib, 2012; Foland-Ross et al, 2013; Gotlib et al, 2004) and adolescents (Hankin et al, 2012; Hommer et al, 2013) show biased processing to affectively negative material compared to healthy controls. We observed greater drift rates in depressed individuals on both correct and error responses (see Figure 2 and Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…This is particularly true during development when the integrity of these pathways is not yet fully formed. Such attentional deficits are reflected in a recent study showing that youth with SMD have an attentional bias to threatening faces compared to controls, and that this bias to threat is associated with higher levels of irritability and symptoms of depression (Hommer et al, 2014). Researchers have also found that children who were rated temperamentally high in anger proneness by parents and teachers, had difficulty moving attention away from rewarding stimuli (He et al, 2013).…”
Section: Emotion Regulation Capacitymentioning
confidence: 99%
“…A small body of research shows that SMD is associated with aberrant emotion-attention interactions, particularly in the context of threat (e.g., Hommer et al 2013). Other studies have shown that SMD is associated with abnormal patterns of neural activation to angry, fearful, and neutral faces compared with that of healthy controls, although findings are contradictory, supporting both hypo-and hyperactivation of the amygdala (Thomas et al 2013(Thomas et al , 2014.…”
mentioning
confidence: 99%